To explore association between gamma-glutamyl transferase and type 2 diabetes using a real-world study and mendelian randomization analysis - Bi, Yaru; Yang, Shuo; Liu, Yanjing; Cao, Lingxia; Gao, Menghan; Liu, Weixia; Li, Yuting; Tian, Suyan; Sun, Chenglin (Frontiers in Endocrinology, 2022)
Aim: The association between gamma-glutamyl transferase (GGT) and type 2 diabetes mellitus (T2DM) is still controversial. The objective of this study was to investigate the association between GGT and the risk of developing T2DM using real-world data, Mendelian randomization (MR) analysis, and literature mining. Methods: The cross-sectional study included 3048 participants (>40 years of age), receiving conventional physical examination in a community in Northeastern China from the year 2019 to 2021. A generalized additive model was used to examine the relation between GGT and T2DM. The causal effect of the GGT on T2DM was assessed by the two-sample MR. Results: GGT is related to glucose metabolism indicators, such as fasting plasma glucose and glycosylated hemoglobin. Odds ratios for T2DM across GGT categories (14–16, 17–20, 21–25, 26–35, ≥36) were 1.159, 1.609, 1.961, 2.120, 2.568 (P＜0.05) versus GGT≤13 categories after adjusting for potential confounders. A generalized additive model identified a nonlinear correlation between GGT and T2DM, and indicated that the risk of T2DM almost levelled out when GGT exceeded 34 IU/L. The MR analysis showed that GGT had no causal effect on T2DM. Conclusions: Although GGT itself cannot cause T2DM, its increment, within a certain range, is indicative of developing T2DM. In summary, GGT screening is recommended in the general population for the early detection of T2DM.